2012
DOI: 10.1039/c2sc01026g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of uncapped nanometre-sized metal particles by decomposition of metal carbonyls in carbon nanotubes

Abstract: Carbonyl complexes of transition metals (M x (CO) y , where x ¼ 1, 2, or 3 and y ¼ 6, 10, or 12 for M ¼ W, Re, or Os, respectively) inserted into single walled carbon nanotubes (SWNT, diameter 1.5 nm) transform into metallic nanoparticles (MNPs) under heat treatment or electron beam irradiation. The host-nanotube acts as an efficient template, controlling the growth of MNPs to $1 nm in diameter. The only co-product of nanoparticle formation, carbon monoxide (CO) gas, creates pockets of high pressure between na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Indeed, a mere temperature increase triggers a drastic chemical transformation in m·[M(CO)6 + In -]@SWNT m+ (Fig 1b,c) as indicated by clear changes in the Raman spectra, where the bands associated with polyiodide are replaced by a new set of bands at lower frequencies indicating a formation of new inorganic species in SWNT nanoreactors (Fig 2l and 3k). High-resolution transmission electron microscopy (HRTEM) imaging of nanotubes after the heat treatment reveals chains of discrete 1 nm clusters uniformly distributed along the nanotube channel (Fig 2a and 3a), which are in stark contrast to the irregular metallic clusters randomly positioned in SWNT that form from M(CO)6 under similar conditions [18]. Aberration-corrected (AC) HRTEM imaging demonstrates a surprisingly well-defined atomic structure of the nanoclusters with a polyhedral geometry which appears to be virtually the same for Mo-and W-containing species (Fig 2h-k and 3c-g).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a mere temperature increase triggers a drastic chemical transformation in m·[M(CO)6 + In -]@SWNT m+ (Fig 1b,c) as indicated by clear changes in the Raman spectra, where the bands associated with polyiodide are replaced by a new set of bands at lower frequencies indicating a formation of new inorganic species in SWNT nanoreactors (Fig 2l and 3k). High-resolution transmission electron microscopy (HRTEM) imaging of nanotubes after the heat treatment reveals chains of discrete 1 nm clusters uniformly distributed along the nanotube channel (Fig 2a and 3a), which are in stark contrast to the irregular metallic clusters randomly positioned in SWNT that form from M(CO)6 under similar conditions [18]. Aberration-corrected (AC) HRTEM imaging demonstrates a surprisingly well-defined atomic structure of the nanoclusters with a polyhedral geometry which appears to be virtually the same for Mo-and W-containing species (Fig 2h-k and 3c-g).…”
Section: Introductionmentioning
confidence: 99%
“…The confinement of individual molecules inside nanoscale containers is a powerful method that allows us to explore chemistry at the single‐molecule level . As the dimensions of the host container approach the size of the encapsulated molecule, the effects of extreme spatial constraint result in changes in van der Waals interactions and electron transfer, leading to new dynamic behaviour and the emergence of physicochemical properties of the confined molecules unattainable in the bulk …”
Section: Introductionmentioning
confidence: 99%
“…[15] Further research has demonstrated that small Os clusters can be inserted into singlewalled carbon nanotubes, which not only stabilize the Os clusters under ambient conditions but also keeps osmium's catalytic activity without being diminished. [16] All of these catalytic activities are strongly dependent on the cluster structure as each small cluster has a different electronic structure. However, there is a lack of experimental and theoretical structural information for Os clusters.…”
Section: Introductionmentioning
confidence: 99%